Possible entry-level positions in selected buying offices for BS Clothing Technology graduates - Plata, Golda Maureen L.; Escano, Maria Monica R. (2001.)
The changing needs of professions in the clothing industry require for continuous assessment of the skills and competencies needed for a particular profession. A research on the various possible entry-level positions, specifically in selected buying offices, awaiting the graduates of the BS Clothing Technology program will help in the understanding of the functions of these positions as well as the skills and qualifications needed to perform them. In return, the study would ensure that the program incorporates the skills and competencies needed for these professions. The main purpose of this study was to determine the possible career opportunities for new BS Clothing Technology (BSCT) graduates in selected buying offices. Specifically, the study aims to determine from the buying offices' point of view the present entry-level positions suited for BSCT graduates. Second, the study aims to determine the specific course subjects in the BSCT program that incorporates the job competencies needed by these entry-level positions in the selected buying offices. I lieu of these objectives, the use of a survey tool was considered in gathering the data for this study. Personal interviews were conducted in four purposively selected buying offices. Consequently, the data collected were presented in descriptive and tabulated forms. Results of this study indicate that the BSCT program incorporates the necessary competencies and training in relation to the job descriptions for an entry-level position in a buying office. However, new BSCT graduates do not immediately assume an executive level position in the selected buying offices. Lastly, merchandising and quality control activities are interconnected since their primary goal is the same --- to ensure quality merchandise to be delivered on time and conforming to the buyer's specifications.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Bachelor of Science in Clothing Technology--Job descriptions